2018
DOI: 10.5004/dwt.2018.22344
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of spatial-temporal evolution of agricultural drought based on regional agricultural drought index

Abstract: a b s t r a c tIn recent years, the frequency and intensity of drought in China are on the rise, and most of the major grain producing provinces are situated in the drought-prone areas, so agricultural drought has become one of the main factors restricting the agricultural production in China. In this paper, with Henan province being taken as the research area, the change trend of agricultural drought area of Henan province was analyzed, and the spatial-temporal evolution characteristics of Henan province were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…In this study, it was found that agricultural drought in Henan Province showed an increasing trend on the whole, and drought was more serious in northern Henan Province and lighter in eastern southern Henan Province, which was consistent with the analysis results of Henan drought by Lu et al [39] based on SPEI and Shang et al [40] based on SPI. Comprehensive analysis shows that regional agricultural drought in Henan Province mainly occurs in northern Henan, central Henan and eastern Henan, which is basically consistent with the analysis results of drought characteristics in Henan Province by Wang et al [41], Li et al [42] and Wang et al [43]. In terms of seasonal scale, spring and autumn are two seasons characterized by frequent droughts, which is in line with the findings of Liu et al [38].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, it was found that agricultural drought in Henan Province showed an increasing trend on the whole, and drought was more serious in northern Henan Province and lighter in eastern southern Henan Province, which was consistent with the analysis results of Henan drought by Lu et al [39] based on SPEI and Shang et al [40] based on SPI. Comprehensive analysis shows that regional agricultural drought in Henan Province mainly occurs in northern Henan, central Henan and eastern Henan, which is basically consistent with the analysis results of drought characteristics in Henan Province by Wang et al [41], Li et al [42] and Wang et al [43]. In terms of seasonal scale, spring and autumn are two seasons characterized by frequent droughts, which is in line with the findings of Liu et al [38].…”
Section: Discussionsupporting
confidence: 88%